in The Development of Social Competence in pre-School Childre The Impact of Using The Think -Pair – Share Strategy (Journal of Hama University, 2019)
The aim of this research is to find out the impact of the use of a strategy (think - Pair – Share) in the development of social competence in preschool children aged 5-6 years. The researcher used the experimental method to answer the hypotheses of the research. The research was applied in the academic year 2018/2019. The research sample consisted of (40) kindergarten children, divided into two groups, one experimental and the other controlled, They were chosen in a deliberate method, Where the experiment was applied by the researcher on the two groups, After the implementation of the educational plan prepared by the researcher and apply the test of social competence and the presentation and interpretation of the results show the following:- There are statistically significant differences between the average scores of the experimental group members in the tribal and remote measurements in the social competence test, in favor of the post-measurement.- There are statistically significant differences between the average scores of the experimental and control groups in the post-measurement to test the social efficiency, in favor of the experimental group.In light of the results, the researcher suggested the following:- Dissemination of a strategic idea (think - Pair – Share) on ​​kindergartens and practice it by teachers.- Teacher training on active learning strategies, especially strategy (think- Pair – Share).